2024
DOI: 10.1111/cpr.13593
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary progenitors facilitate cardiac repair via exosomal transfer of miR‐27b‐3p targeting the SIK1‐CREB1 axis

Ying‐Ying Xiao,
Luo‐Xing Xia,
Wen‐Jing Jiang
et al.

Abstract: Ischemic heart disease, especially myocardial infarction (MI), is one of the leading causes of death worldwide, and desperately needs effective treatments, such as cell therapy. Cardiopulmonary progenitors (CPPs) are stem cells for both heart and lung, but their repairing role in damaged heart is still unknown. Here, we obtained CPPs from E9.5 mouse embryos, maintained their stemness while expanding, and identified their characteristics by scRNA‐seq, flow cytometry, quantitative reverse transcription‐polymeras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…SIKs also involve in the pathological cardiac remodeling following myocardial infarction (MI). A recent study reported that intramyocardial transplantation of embryonic cardiopulmonary progenitors can target the SIK1-CREB1 axis via exosomal transfer of miR-27b-3p to facilitate cardiac repair and improve cardiac function in a mouse model of MI ( Xiao et al, 2024 ). Ischemia-reperfusion (IR) injury induces the expression of SIK2 in myocardial tissues ( Liu et al, 2022 ).…”
Section: Cardiac Hypertrophy and Ischemiamentioning
confidence: 99%
“…SIKs also involve in the pathological cardiac remodeling following myocardial infarction (MI). A recent study reported that intramyocardial transplantation of embryonic cardiopulmonary progenitors can target the SIK1-CREB1 axis via exosomal transfer of miR-27b-3p to facilitate cardiac repair and improve cardiac function in a mouse model of MI ( Xiao et al, 2024 ). Ischemia-reperfusion (IR) injury induces the expression of SIK2 in myocardial tissues ( Liu et al, 2022 ).…”
Section: Cardiac Hypertrophy and Ischemiamentioning
confidence: 99%